Resisting Heteropatriarchy: Gender Performativity in Instagram Narratives - Secilia Wilma Octaviani; Fabianus Fensi (Ikatan Sarjana Komunikasi Indonesia, 2025)
In heteropatriarchal societies, women are often shaped to internalize normative expectations regarding love and marriage. This article analysis a personal narrative shared through the Instagram account @lovecoach.id, which depicts experiences of trauma, delayed marriage, and concerns about harmful relationships. The study was conducted over a five-month period (April–September 2025). The data source was the Instagram account @lovecoach.id. The study aims to examine how this narrative can be understood as a form of gender performativity and resistance to heteropatriarchal norms that position women as passive subjects within the institution of marriage. Employing a qualitative approach and critical discourse analysis grounded in Judith Butler’s theoretical framework, this study explores how gender identity is produced and negotiated through language and digital media. The findings reveal that the narrative not only expresses an individual experience but also represents a broader rejection of social constructions surrounding women’s obligation to marry. Expressions of trauma, emotional unpreparedness, and aspirations for egalitarian relationships signal subversive gender practices that challenge dominant norms. This research underscores the significance of social media as an articulative space for women to construct gender identities autonomously and reflectively, while simultaneously rejecting hegemonic narratives of love and marriage.